1996
DOI: 10.1007/s002620050244
|View full text |Cite
|
Sign up to set email alerts
|

Disregulation in TH1 and TH2 subsets of CD4 + T cells in peripheral blood of colorectal cancer patients and involvement in cancer establishment and progression

Abstract: Recent theories have established that, during an ongoing immune response, the lymphokines produced by TH1 and TH2 subsets of CD4+ T cells are critical to the effectiveness of that response. In vivo and in vitro studies have demonstrated that the type of environmental cytokines plays a determinant role in directing the development of naive T cells into TH1 or TH2 effector cells. Disregulated expansion of one or other subset may contribute to the development of certain diseases. To establish whether a similar si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(83 citation statements)
references
References 33 publications
5
77
1
Order By: Relevance
“…The type of immune response might be influenced by the neoplasia as well. Indeed, Pellegrini et al showed that in peripheral blood cells of patients with colorectal cancer, there was a dysregulation in the functionality of Th1 and Th2 cells, with an expansion in Th2 and a malfunction in Th1 cells [29]. It is of note that we observed no correlation between the evolution in cellular immune response directed against tuberculin and the clinical outcome of patients treated with BCG instillations [8].…”
Section: Discussioncontrasting
confidence: 47%
“…The type of immune response might be influenced by the neoplasia as well. Indeed, Pellegrini et al showed that in peripheral blood cells of patients with colorectal cancer, there was a dysregulation in the functionality of Th1 and Th2 cells, with an expansion in Th2 and a malfunction in Th1 cells [29]. It is of note that we observed no correlation between the evolution in cellular immune response directed against tuberculin and the clinical outcome of patients treated with BCG instillations [8].…”
Section: Discussioncontrasting
confidence: 47%
“…Usually, the tumor microenvironment is immunosuppressive, with presence of IL-10 and TGF-b, which induces regulatory T cell responses and reduces the prevalence of Th1 CD4 + T cells. This shifts the Th1/Th2 immune balance, and the immunosuppressive nature of these cells can lead to tolerance against tumor Ags or pathogens (43,44). IL-10 2/2 mice, compared with wild-type mice, develop severe gastritis when infected with H. pylori bacteria; therefore, IL-10 may have a potential role in downregulating H. pylori-induced inflammation at the site of infection (45).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that there is decreased IL-2 production and elevated IL-4, IL-6, and IL-10 production in colorectal cancer, decreased IL-2 and IFN-γ production in bladder cancer, prostate cancer, and renal cancer and increased IL-10 mRNA expression in lung cancer [8,[14][15][16][17]. Expression of the Th2 type cytokine IL-6 within esophageal cancer tissue is known to be profoundly associated with the progression of esophageal cancer and poor prognosis [18,19].…”
Section: Pstage (Tnm Classification)mentioning
confidence: 99%